2010
DOI: 10.1111/j.1477-9552.2009.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Nutrition Claims Matter to Consumers? An Empirical Analysis Considering European Requirements

Abstract: EU Regulation 1924/2006 introduced a European legal framework for nutrition messages for food product labels. The study analyses consumer interest towards nutrition labelling and claims, and examines the information consumers consider important during their purchasing decisions, and the main characteristics of those consumers interested in nutrition claims and nutrition labelling use. A total of 1,025 northern Italian consumers were surveyed. We estimate one binary logit model to investigate the use of nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Barreiro-Hurle, Gracia, and de-Magistris (2010) demonstrated that the use of nutrition information influenced consumers' choice of healthier food products, although different types of label information were used by different types of consumers. Also Stranieri, Baldi, and Banterle (2010) showed that the characteristics of consumers who use nutrition label information (e.g. higher interest in food safety, specific dietary habits and higher age) differ from those who don't use such information.…”
Section: Introductionmentioning
confidence: 98%
“…Barreiro-Hurle, Gracia, and de-Magistris (2010) demonstrated that the use of nutrition information influenced consumers' choice of healthier food products, although different types of label information were used by different types of consumers. Also Stranieri, Baldi, and Banterle (2010) showed that the characteristics of consumers who use nutrition label information (e.g. higher interest in food safety, specific dietary habits and higher age) differ from those who don't use such information.…”
Section: Introductionmentioning
confidence: 98%
“…Consumer WTP is expected to increase as income of the consumer increases (Teratanavat and Hooker, 2006;Liu et al 2009) due to negative correlation between consumer WTP for food safety and marginal utility of money. In contrast, Stranieri et al (2010) found a negative relationship between consumers' income and their nutritional claims, the possible reason been that the time pressure of high-income consumers tend to affect their information use on nutrition labels. This therefore makes the effect of income on consumer WTP inclusive in the empirical literature.…”
Section: Introductionmentioning
confidence: 61%
“…The ϕ's assume a standard normal distribution (Greene, 2008 (Barrena and Sanchez, 2010;Stranieri et al 2010). Liu et al (2009) posit that after the consumer's age has increased beyond a certain threshold, the WTP tends to decrease with age.…”
Section: Consumer Willingness To Pay a Premium For A Functional Food mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such changes in perceived healthiness were not likely to persuade food choice and eating. Stranieri et al (2010) examined the buyer's interest towards nutrition labeling, nutritional claims, the information consumers believed to be essential during their purchasing choices and the core uniqueness of those consumers interested in nutrition claims and nutrition labeling use. The results showed that nutrition labeling was a vital tool for product choice.…”
Section: Introductionmentioning
confidence: 99%